Peran Citra Tubuh Terhadap Kepercayaan Diri Pada Remaja Perempuan di Denpasar Yang Menggunakan Media Sosial Tiktok - Kusumawati, Ni Ayu Diah; Marheni, Adijanti; Suarya, Luh Made Karisma Sukmayanti (Jurnal Ilmiah Wahana Pendidikan, 2025)
Self-confidence is one of the important things in the growth and development process, especially in adolescents. This is because self-confidence is one of the developmental tasks in adolescence. where at this stage individuals will experience various changes in themselves, starting from physically and psychologically, not infrequently these changes cause adolescents' self-confidence to decrease. Body image at this time is often based on stereotypes or certain beauty standards such as having a good body shape, being thin, having a tall body and white skin which are spread through TikTok social media. This study aims to determine the role of body image on self-confidence in female students in Denpasar who use TikTok. This type of research is quantitative using cluster sampling techniques. The measuring instrument used in this study uses a scale of self-confidence and body image. The total number of subjects in this study was 197 respondents. Data analysis in this study used a simple linear regression technique. The results of the study showed that appearance evaluation played a role of 11.3% on self-confidence, appearance orientation played a role of 8.6% on self-confidence, satisfaction with body parts played a role of 6.4% on self-confidence, anxiety about having a fat body played a role of 0.3% so it was considered not to play a role on self-confidence and body size categorization played a role of 2.3% on self-confidence.